A SECURE FILE ENCRYPTION AND DECRYPTION SYSTEM USING AES FOR TEXT AND IMAGES - Banga, Pranav; Nirottam; singh, Shubham Kumar; Shubham; Singh, Priyanka (International Journal of Research -GRANTHAALAYAH, 2023)
In today’s digital era, where vast amounts of sensitive data are transmitted over the internet, securing this information from unauthorized access has become a major concern. The rise of cyber threats and data theft calls for robust protection mechanisms, among which encryption stands out as a fundamental solution. This project focuses on developing a secure file encryption and decryption system using the Advanced Encryption Standard (AES) algorithm for both text and image data. AES is a symmetric encryption technique known for its speed, efficiency, and strong security. It outperforms older algorithms like DES and RSA in both performance and reliability. The system proposed in this project employs AES to encrypt and decrypt both text and image files, ensuring confidentiality and integrity during transmission. Encryption converts plaintext into unreadable ciphertext using a secret key, while decryption reverses the process with the same key, making it accessible only to authorized users. The system is implemented in Java and features a user-friendly interface for securely encrypting data. It incorporates a mechanism where a random image is used in the encryption phase and the original image is restored during decryption. This approach adds an extra layer of complexity and security, making brute-force or unauthorized deciphering extremely difficult. Furthermore, the project discusses the challenges in image encryption, including data redundancy and pixel correlation, and how AES effectively overcomes these. It also highlights the suitability of AES for multimedia data and emphasizes the reliability of sharing encrypted data, particularly images, over unsecured networks. By integrating AES with image handling and applying a systematic encryption-decryption framework, the proposed system provides an effective solution for secure communication in modern digital environments.